2021
DOI: 10.1016/j.radcr.2020.12.013
|View full text |Cite|
|
Sign up to set email alerts
|

Cavernous sinus thrombosis in a COVID-19 patient: A case report

Abstract: Coronavirus disease 2019 (COVID-19) is an emerged pandemic disease caused by a new coronavirus known as SARS-CoV-2 (severe acute respiratory syndrome-coronavirus-2). Initially the mortality of this infection are related to severe acute respiratory distress syndrome, but several publications also showed that this infection caused an inflammatory response with severe systemic complications [1] . Venous thromboembolism has been shown to be an important cause of morbidity and mortality in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
2
15
0
2
Order By: Relevance
“…As previously discussed, the association of CVT with COVID-19 has attracted interest from neurologists. Table 1 summarizes the clinical characteristics of the CVT cases associated with CVT that have been reported [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , 32 , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ]. Hughes et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed, the association of CVT with COVID-19 has attracted interest from neurologists. Table 1 summarizes the clinical characteristics of the CVT cases associated with CVT that have been reported [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , 32 , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ]. Hughes et al.…”
Section: Resultsmentioning
confidence: 99%
“…[ 71 ] 43/F Eight days Levetiracetam, hydroxychloroquine, low molecular weight heparin, oseltamivir and ceftriaxone Improved Khacha et al. [ 72 ] 55/M A few days Infused heparin and acenocoumarol Improved Mowla et al. [ 73 ] 13 patients A few days Anticoagulant therapy Six patients discharged with good outcomes and three died Nwajei et al.…”
Section: Resultsmentioning
confidence: 99%
“…An otherwise rare fungal infection, the increase in CAM cases has predisposed patients to multiple presentations of invasive fungal disease. In association with CAM, cavernous sinus thrombosis has only been reported as isolated case studies [3] [4]. However, no studies have studied the risk factors and outcomes in cavernous sinus thrombosis in CAM.…”
Section: Introductionmentioning
confidence: 99%
“…10 COVID-19 is known to have a hypercoagulable presentation along with increased fibrinogen and D-dimers blood levels. [17][18][19][20] This may lead to an increased incidence of cerebral venous sinus thrombosis (CVST) in such cases. 19,20 Other inflammatory markers may also be higher in patients with ocular symptoms as compared to those without any.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] This may lead to an increased incidence of cerebral venous sinus thrombosis (CVST) in such cases. 19,20 Other inflammatory markers may also be higher in patients with ocular symptoms as compared to those without any. 1,3,9,10,[18][19][20][21][22][23][24] Recent studies have reported a new spectacle of this disease spectrum in the form of rhino-orbital mucormycosis.…”
Section: Introductionmentioning
confidence: 99%